2014
DOI: 10.1111/ajr.12076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a rural nurse-led clinic for female sexual dysfunction

Abstract: This study confirmed the value of an innovative approach to managing female sexual dysfunction in a rural area with workforce shortages and limited health services. It is recommended that care by a nurse-led multidisciplinary team be used in the management of sexual dysfunction. Further research is needed to see if this model of care would be effective in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(30 reference statements)
2
2
0
Order By: Relevance
“…The demonstrated benefit of nurse‐led care in reducing HbA1c in adults with diabetes from this review is consistent with reported benefits of nurse‐led clinics that involve other conditions and diseases (Anonymous, 2013; Gow et al, 2014; Hakanson et al, 2014; Keleher et al, 2009; Marshall et al, 2011; Stirling et al, 2016; Wong & Chung, 2006). Worldwide, in countries including Australia, Canada, New Zealand, Sweden, the United Kingdom and United States of America, nurse‐led clinics in areas as diverse as ear, nose and throat, memory, rheumatology, Parkinson's and sexual dysfunction have been shown to improve clinical outcomes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The demonstrated benefit of nurse‐led care in reducing HbA1c in adults with diabetes from this review is consistent with reported benefits of nurse‐led clinics that involve other conditions and diseases (Anonymous, 2013; Gow et al, 2014; Hakanson et al, 2014; Keleher et al, 2009; Marshall et al, 2011; Stirling et al, 2016; Wong & Chung, 2006). Worldwide, in countries including Australia, Canada, New Zealand, Sweden, the United Kingdom and United States of America, nurse‐led clinics in areas as diverse as ear, nose and throat, memory, rheumatology, Parkinson's and sexual dysfunction have been shown to improve clinical outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…The demonstrated benefit of nurse-led care in reducing HbA1c in adults with diabetes from this review is consistent with reported benefits of nurse-led clinics that involve other conditions and diseases (Anonymous, 2013;Gow et al, 2014;Hakanson et al, 2014;Keleher et al, 2009;Marshall et al, 2011;Stirling et al, 2016;Wong & Chung, 2006) (King et al, 2019). With the increasing burden of diabetes and government reforms shifting care from tertiary to primary health-care settings, changes to applicable nursing curricula should be considered.…”
Section: Discussionsupporting
confidence: 79%
“…The model consists of four levels: Ppermission, LI -limited information, SS -specific suggestions, IT -Intensive Therapy (Taylor & Davis, 2006). Talking about sexuality with individuals with sexual problems and encouraging sexual practices with safe counseling serviceswill be of significant benefit to health professionals for identifying and resolving existing or possible sexual problems (Hakanson, Douglas, Robertson, & Lester, 2014). Therefore, this systematic review aimed to find out the effects of the PLISSIT model on sexual functions.…”
Section: Introductionmentioning
confidence: 99%
“…Se debe plantear la importancia de que los profesionales de la salud, conocedores de anatomía y fisiología, hagan algo básico que podría llamarse «puericultura sexual» con sus pacientes. En el mundo existen experiencias muy interesantes sobre educación sexual, no solo con médicos, sino con enfermeras, aun en áreas rurales, enfocadas a la sexualidad, que ayudan a mejorar la calidad de vida de las comunidades 49 .…”
Section: Recomendacionesunclassified